156 A single centre experience of Ivabradine and Clonidine for inappropriate sinus tachycardia. (9th June 2011) - Sadarmin, P P; Betts, T R
Abstract : Introduction: Inappropriate sinus tachycardia (IST) is a relatively rare disease that manifests with resting tachycardia, a rapid increase in heart rate (HR) with minimal exertion, a normal ECG and absence of structural heart disease. Treatment options include β-blockade or sinus node modification which are not 100% successful. Newer agents like sinus node inhibitor (Ivabradine) or a centrally acting α-2 sympathomimetic (Clonidine) can be used but there is no success outcome data for either and there is also no evidence that one is better than the other. We present our experience of managing 6 patients with a diagnosis of IST with either Ivabradine or Clonidine or both. Methods: We identified 6 patients from 2005 to 2009 with a diagnosis of IST (according to accepted international guidelines) who had been treated with either Ivabradine or Clonidine or both. Medical case records were reviewed for each patient. Results: 5 out of 6 patients were women with a mean age of 27.5 years (range 16–40 years). All patients had been symptomatic for alteast 6 months before presentation to our tertiary centre. 2 patients had associated symptoms of hyperadrenergic surges. Holter monitoring prior to treatment demonstrated sinus tachycardia. Resting pre-treatment mean 24 h HR was 94±10 (range 75–100) and mean HR on minimal exertion was 157±20 (range 130–176). All patients had a structurally normal heart on echocardiogram. Tilt table testing was considered in 3 patients due to their symptoms and it excluded postural orthostatic tachycardia syndrome. Pre-treatment with β-blockers had been unsuccessful in 5/6 patients. The remaining patient had symptomatic asthma and was therefore unable to tolerate β-blockers. Ivabradine was exclusively used in 3 patients and clonidine in 2. 1 patient was started with Ivabradine but later switched over to clonidine as it was ineffective. All 4 patients taking Ivabradine failed to gain symptom relief with no significant reduction in mean 24-h HR parameters. Mean resting HR after 3 months of Ivabradine therapy was 95±9 (range 88–105) and mean HR on exertion was 159±23 (range 128–180). 2/4 patients subsequently had complete sinus node ablation and AAIR pacemaker. In contrast, the 3 patients on clonidine had greater symptom resolution and fall in resting and exercise heart rates at 3 months follow-up. Resting mean HR was 81±3 (range 78–83) and mean HR with exertion was 144±18 (range 132–164). The HR variability pre and post treatment is shown in Abstract 156 figure 1 . Discussion: In our case series of 6 patients, Clonidine was more effective than Ivabradine both in terms of reducing heart rate and treating symptoms for patients with inappropriate sinus tachycardia. Patients with coexisting hyperadrenergic symptoms may benefit the most. A trial of Clonidine can be recommended before considering sinus node ablation. Formal randomised controlled trials are needed to confirm our findings.